The Effect of Implant Failure After Symphyseal Plating on Functional Outcome and General Health. Issue 6 (June 2016) - Frietman, Bas; Verbeek, Jan; Biert, Jan; Frölke, Jan-Paul
Abstract : Objectives: To relate the incidence of implant failure after internal anterior fixation of the pelvic ring to functional outcome and the health-related quality of life in patients. Design: Retrospective chart and radiographic review. Setting: Level I Trauma center. Methods: We retrospectively identified all patients who were treated with symphyseal plating for traumatic symphyseal diastasis between January 2003 and December 2013. Patients were asked to complete 2 questionnaires, the SF-36 and the Majeed score. A retrospective chart and radiographic control review were performed on all patients. The following data were collected: demographic data and details regarding the pelvic surgery. Computed tomograms were used to determine fracture classification and quality of reduction. Conventional radiographic follow-up were used to detect implant failure. Results: A total of 37 patients enrolled the study. Implant failure occurred in 11 (30%) patients resulting in the identification of 2 groups, "implant failure" (n = 11) and "intact implants" (n = 26). The baseline characteristics were equal in both groups. The analysis of the questionnaires revealed that the SF-36 score was not significantly different in any of the dimensions between the both groups. Patients in the implant failure group scored higher on all of the Majeed items, including the total Majeed score, but the difference did not reach statistical significance of P < 0.05. Conclusions: Our study showed comparable results regarding the general health measured by the SF-36 for both groups and higher Majeed scores for patients with implant failure compared with patients with intact implants. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.